FRI0639-HPR Gender Differences in Acute Influence of Restricted Ankle Dorsiflexion Angle on Knee Adduction Moment during Gait. (15th July 2016) - Fujita, R.; Ota, S.; Ueda, M.; Aimoto, K.; Nakanishi, A.
Abstract : Background: Ankle dorsiflexion (DF) is necessary during terminal stance of gait, and its restricted range leads to increased knee adduction moment (KAM) in a previous report. Females are found to have a greater decrease in DF than males across age groups (every 5 years from 55 to 85 years old). Female gender is one of the critical risk factors of advanced and symptomatic medial knee osteoarthritis (knee OA). From this point of view, restricting the ankle range of motion is thought to be more related to increase the risk of knee OA in female compared to the risk in male. However, it is not clear whether there are gender differences in the influence of restricted ankle dorsiflexion angle on KAM during gait. Objectives: The purpose of the present study was to investigate gender differences in KAM during the terminal stance of gait between unrestricted and restricted ankle range of motion. Methods: Forty-nine healthy volunteers (24 males, 25 females) walked with a custom-designed ankle brace that restricted ankle DF. Kinematics and kinetics were collected using a 7-camera motion analysis system and two force plates. Ankle DF was unrestricted and restricted to 0 degree. Ankle DF angle, knee extension angle and KAM were measured during terminal stance. The significant difference was set for both conditions of p<0.05 and above 0.50 effect size (ES) in the present study. Results: Peak ankle DF angles for unrestricted and restricted by the brace were 13.9 ± 4.1° and 7.0 ± 5.4° in males, and 10.1 ± 5.6° and 2.8 ± 4.1° in females, and peak knee extension angles were −9.0 ± 4.8° and −4.0 ± 6.4° in males, and −3.2 ± 5.2° and 2.0 ± 5.7° in female, respectively. The peak KAMs were 0.38 ± 0.15 Nm/kg and 0.42 ± 0.15 Nm/kg in males (p=0.018, ES =0.27), and 0.37 ± 0.12 Nm/kg and 0.47 ± 0.12 Nm/kg in females (p<0.001, ES =0.83). KAM was significantly different between unrestricted and restricted ankle range of motion in females. In both genders, significant correlations were observed between the changes with both conditions in KAM and changes in peak knee extension angle. A stronger relationship was observed between them in females than in males (r=0.52, p=0.012 in males, r=0.64, p=0.001 in females). Significant correlations were observed between changes in peak knee extension angle and changes in peak ankle DF angle in males (r=−0.65, p=0.001), but no relationship was observed in females. Conclusions: KAM in females was more affected by restricted ankle DF during terminal stance of gait than KAM in males. Increased KAM was related to greater knee extension angle, which may be caused by restricted ankle DF. However, knee extension angle in female is assumed to be affected by the genu recurvatum observed during the restricted ankle range of motion condition and the ceiling effect shown in the relationship with changes in peak ankle DF angle. Disclosure of Interest: None declared